Humanistic Multicultural Analysis in Shaping Tolerance Culture Among Students in Islamic Education Learning - Bahri, Ahmad; Rizquha, Ach (Universitas Nurul Jadid, 2023)
This study aims to explore the development of humanistic multicultural education within the framework of Islamic Religious Education (PAI) at Junior high school, focusing on its role in fostering a culture of tolerance among students. Given the increasing importance of multicultural values in diverse educational settings, this research addresses the integration of these values in PAI learning. Employing a qualitative research method with a purposive sampling approach, the study examines the alignment of educational objectives, materials, methods, and evaluation as outlined in the syllabus. The findings reveal that humanistic multicultural values are effectively integrated into PAI, contributing to the promotion of tolerance through both curriculum content and the exemplary behavior of PAI and other subject teachers. This research provides insights into how Islamic Religious Education can be a vital tool in cultivating a tolerant and inclusive school environment.